Circadian hemodynamic characteristics in hypertensive patients with primary aldosteronism. Issue 11 (November 2018) - Kusunoki, Hiroshi; Iwashima, Yoshio; Kawano, Yuhei; Hayashi, Shin-ichiro; Kishida, Masatsugu; Horio, Takeshi; Shinmura, Ken; Yoshihara, Fumiki
Abstract : Objective: The present study aimed to compare circadian hemodynamic characteristics in hypertensive patients with and without primary aldosteronism. Methods: Circadian hemodynamics, including 24-h brachial and central blood pressure (BP), SBP variability indices, central pulse wave velocity (PWV), augmentation index (AIx@75), cardiac index, and total vascular resistance (TVR), were evaluated using an oscillometric device, Mobil-O-Graph, in 60 patients with primary aldosteronism (63.4±13.3 years, 47% women) and 120 age-matched and sex-matched patients with essential hypertension. Results: Office SBP, PWV, AIx@75, and BP variability indices were similar between groups; however, 24-h brachial (124 ± 14 vs 130 ± 11 mmHg) as well as central (112 ± 12 vs 120 ± 10 mmHg) SBP was higher (both P < 0.01), and the difference between 24-h brachial and central SBP (11 ± 5 vs 9 ± 3 mmHg, P < 0.05), an index of pressure amplification, was smaller in primary aldosteronism than in essential hypertension. In both groups, cardiac index decreased from daytime to night-time (both P < 0.01), but this decrease was smaller in primary aldosteronism ( P < 0.05). During daytime, TVR in primary aldosteronism was higher than that in essential hypertension ( P < 0.05), and the significant increase of TVR from daytime to night-time was lost in primary aldosteronism. In a multivariate stepwise regression model, primary aldosteronism emerged as an independent predictor of 24-h central SBP as well as the difference between 24-h brachial and central SBP. Conclusion: Our results demonstrated that circadian hemodynamics in primary aldosteronism patients are characterized by increased central SBP, smaller disparity between brachial and central SBP, and disturbed circadian hemodynamic variation.